Hydrogen production by semicoke gasification with a supercritical water fluidized bed reactor. (28th September 2016) - Cheng, Zening; Jin, Hui; Liu, Shanke; Guo, Liejin; Xu, Jialing; Su, Di
Abstract: Semicoke powders with particle size less than 6 mm are by-products during the pyrolysis of coal. Direct combustion of semicoke powders is difficult due to the low volatile content. Supercritical water gasification might provide an efficient conversion method for semicoke powders. In order to determine the optimum conditions of gasification of semicoke with the supercritical water fluidized bed reactor, the influences of the main operating parameters including temperature (540–660 °C), feedstock concentration (10–30 wt%), flow rate of preheated water (40–80 g/min) and alkali catalysts (K2 CO3, KOH, Na2 CO3 and NaOH) were systematically investigated in this study. The results showed that semicoke-water slurry of 30 wt% was continuously transported into the reactor and stably gasified without plugging problems. Hydrogen yield of 85.90 mol/kg was obtained with the hydrogen molar fraction of 61.02%. In particular, carbon gasification efficiency of more than 95% was obtained under the conditions of 660 °C, 60 g/min flow rate of preheated water and 10 wt% feedstock concentration with 5 wt% K2 CO3 . Highlights: This was the first time supercritical water was applied to gasify semicoke. Semicoke-water slurry of 30 wt% was continuously transported into the reactor. 600 °C might be the trigger temperature for fixed carbon complete gasification. Carbon gasification efficiency of more than 95% was obtained.